Contemporary drawing : key concepts and techniques - Davidson, Margaret (New York : Watson-Guptill Publications, 2011)
Looks at drawing's renewal of importance in the art world through illuminating discussion. This title is suitable for beginner to professional-level artists seeking advanced explorations of the foundations of drawing. It is illustrated by specific drawing examples & techniques by modern era masters & leading contemporary artists
1. Surface -- 2. Mark -- 3. Space -- 4. Composition -- 5. Scale -- 6. Materials -- 7. Breaking barriers -- 8. Intentionality
Includes bibliographical references (p. 188-189) and index
Keywords: Drawing -- Technique